The Polish Committee for Sports Events in Berlin on the Road to Normalisation of Polish-German Political Relations (1932–1934). The Political Background of the First-Ever Football Match between the Polish and German National Teams - Jung, Rafał (International Studies. Interdisciplinary Political and Cultural Journal, 2022)
The article discusses a unique Polish-state institution functioning in the interwar period, the Polish Committee for Sports Events in Berlin (PKISB). Through sport, its representatives channelled the ambition to shape Poland’s favourable image in the German Reich which was hostile to the Second Polish Republic. In the long run, the Committee proved to be an instrument for improving general Polish-German relations. The article focuses on an initial phase of PKISB activity, when, after Adolf Hitler came to power, the future of political relations between the hitherto antagonised neighbours was at stake. The activities of this institution have been analysed mainly with reference to football as the most popular sport in Poland and Germany.